2012
DOI: 10.1049/el.2011.3133
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of electromagnetic properties in iron-mine production tunnels

Abstract: Modern underground mines require reliable wireless communication for transmitting voice data, operating surveillance cameras, and monitoring mining equipment such as heavy vehicles. The electromagnetic characteristics of mines therefore have to be considered when determining the type of wireless technology for such critical applications. In this reported work, measurements of radio interference levels, path loss, and multipath propagation are performed in the world's now largest iron ore mine, situated in Swed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Numerous papers have investigated the propagation in 'non-subway' tunnel environments: [2][3][4] focus on the high-speed railway and highway tunnels. These tunnels are usually of large transverse dimensions, which is quite different from the subway condition, and the measurements in [2][3][4] were not conducted by a real moving subway train therefore the effect of the train was not considered in the analysis, so that the results cannot provide reliable guidelines for subway tunnel communications; [5][6][7][8] aim at the underground mine tunnels. These tunnels are usually very small and only allow the human's mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous papers have investigated the propagation in 'non-subway' tunnel environments: [2][3][4] focus on the high-speed railway and highway tunnels. These tunnels are usually of large transverse dimensions, which is quite different from the subway condition, and the measurements in [2][3][4] were not conducted by a real moving subway train therefore the effect of the train was not considered in the analysis, so that the results cannot provide reliable guidelines for subway tunnel communications; [5][6][7][8] aim at the underground mine tunnels. These tunnels are usually very small and only allow the human's mobility.…”
Section: Introductionmentioning
confidence: 99%
“…In [13], the authors proposed a multimode model for predicting the received power and the PDP in tunnels with pillars. The analysis of measurements performed in wide and narrow iron-mine tunnels [14] show a small delay spread even in NLOS scenarios. The work in [15] analyzed the channel of an underground gold mine, and found that the RMS delay spread is decreasing with distance.…”
Section: A Overview Of Measurements Campaignsmentioning
confidence: 96%
“…Multipath propagation has been studied and characterized in a multitude of environments, such as residential buildings, indoor offices and mines. The work performed in [6] proposes statistical models for estimating the root-mean-square (RMS) delay spread, path-loss and other relevant propagation [10] 1.89 0.5 298 Paper mill [10] 1.89 0.5 23 Subway tunnel [11] 2.4 0.1 159-234 Road tunnel [12] 5.2 0.1 20-100 Mine tunnel [13] 1 0.2 20-50 Mine tunnel [14] 2.4 0.5 14 Mine tunnel [15] 2.4 0.2 27.4 Mine tunnel [16] 2.4/5.8 0.2 1-15 Mine tunnel [17] 3.5 3 11-29 Mine tunnel [18] 2.4 0.2 1.7 LiU tunnel 3.5 2 3-16…”
Section: A Overview Of Measurements Campaignsmentioning
confidence: 99%
“…Exactly there the most negative effects of "locomotive -wagon" collisions manifest themselves [10]. Analysis of the dynamic forces occurring in couplings during train acceleration and deceleration is presented in work [11], but the influence of the system parameters on emergence of oscillatory processes taking place in it was not shown. The conditions of underground hauling make it practically impossible to manage these works in a manual way.…”
Section: Development Of a System To Control The Motion Of Electric Trmentioning
confidence: 99%
“…From an operational point of view, the operations of wagon moving should be carried out in a minimum time which will increase productivity. Thus, it is necessary to synthesize an electric train control algorithm which is optimal for speed of operation [11]. The equation of the train movement is described by the differential equation:…”
Section: Fig 2 Block Diagram Of the Algorithm For Eliminating Oscilmentioning
confidence: 99%